1973
DOI: 10.1037/h0034501
|View full text |Cite
|
Sign up to set email alerts
|

The need to affiliate and self-esteem in institutionalized children.

Abstract: The present experiment was designed to test the hypothesis that institutionalized children have a greater need to affiliate, compared to noninstitutionalized control children, and that this need is negative in nature. It was also predicted that institutionalized children manifest less self-esteem than control subjects and that self-esteem is related to affiliation. An adaptation of French's Test of Insight and the Personal, Home, Social and Formal Relations Questionnaire were administered to 12 male and 12 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…The lower self-esteem observed in institutionalized children was in line with previous studies. Parental and subsequent social deprivation associated with institutionalization and the necessity to redefine themselves and to adapt their identity make many institutionalized children and adolescents feel insecure, lonely, and worthless, which in turn impairs their self-acceptance, self-confidence, and self-esteem (15, 53–56). However, also, non-institutionalized children who lost one or both parents need to overcome the loss and have to go through a long process of adaptation and redefinition of their self-concept, which likely decreases their self-esteem and other facets of their psychological adjustment (30, 31, 54).…”
Section: Discussionmentioning
confidence: 99%
“…The lower self-esteem observed in institutionalized children was in line with previous studies. Parental and subsequent social deprivation associated with institutionalization and the necessity to redefine themselves and to adapt their identity make many institutionalized children and adolescents feel insecure, lonely, and worthless, which in turn impairs their self-acceptance, self-confidence, and self-esteem (15, 53–56). However, also, non-institutionalized children who lost one or both parents need to overcome the loss and have to go through a long process of adaptation and redefinition of their self-concept, which likely decreases their self-esteem and other facets of their psychological adjustment (30, 31, 54).…”
Section: Discussionmentioning
confidence: 99%
“…In the studies conducted on the adolescents in institutional care, it is known that the self-confidence of these individuals is lower compared with their peers living with their parents (Asif, 2017;Fawzy, & Fouad, 2010;Priyanka, Parasar, & Dewangan, 2018;Youngleson, 1973). The self-confidence of adolescents in institutional care may be negatively affected due to their traumatic experiences.…”
Section: Discussionmentioning
confidence: 99%
“…And again victimization by peers, parental emotional neglect, childhood sexual abuse, insecure attachment, anxiety, depression, low selfesteem, body dissatisfaction, poor school achievement, drug consumption, dissociative symptoms, and general psychopathology are well said to be associated with the SM (Brodsky, Bjärehed &Lundh, 1995 and. Youngleson, (1973) investigated study comparing 24 institutionalized children and a matched control group, and the findings show that institutionalized children were less well put up in the self-concept and that they manifest less self-esteem so much so more prone to self-harming behaviour and are less adjusted compared with a control group. Tizard and Hodges, (1978) extended the study between 65 of the institutionalized and 26 formerly institutionalized children showed that significant differences were found between institutionalized or previously institutionalized children and their non-institutionalized counterparts on total problem behaviours and anti-social scores.…”
Section: Self-concept and Self-mutilationmentioning
confidence: 94%